Tobacco 21 Laws, Prenatal Smoking, and Birth Outcomes - James Flynn (Institute of Labor Economics (IZA), 2025)
This paper examines the effect of Tobacco 21 laws, which raise the minimum age for tobacco purchases to 21, on prenatal smoking and birth outcomes using restricted access data from the National Vital Statistics System. Using both the synthetic difference-in-differences and stacked event-study designs, I fail to find evidence that these laws reduced prenatal smoking or cause any improvement on birth outcomes. I am able to rule out even modest decreases in prenatal smoking of greater than 6% on the extensive margin and greater than 5% on the intensive margin. Results are unchanged if I focus only on non-high school graduate mothers, who smoke at much higher rates at baseline, or if I focus solely on states which passed the toughest laws. My findings suggest that T21 laws may not be an effective policy tool to prevent prenatal smoking.
Keywords: I12; I18; 330; Tobacco 21; prenatal smoking; minimum legal sale age